Understanding Theology : volume 1 ; the means of developing a healthy Church in the twenty first century - Kendall, R. T. (Great Britain : Christian Focus Publications, 1996)
"Theology professor and former pastor presents concise overview of 40 theological concepts for lay readers"--Provided by publisher.
Includes index.
Keywords: Theology, Doctrinal